Economic freedom, real exchange rates and economic growth in emerging markets and developing countries - Mohd Ali, Ly Slesman @ Sulaiman; Niaz Ahmad, Mohd Naseem; Aldomi, Ra'ed Fuad Mahmoud (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
This paper examines the contingency effects of economic freedom on the growth effect of the exchange rate in a panel of 83 emerging markets and developing countries over the period 1976-2010. Based on the generalized method of moments system estimators (SGMM) that control for the weakness and proliferation of instruments, we uncover positive and significant contingency effects of economic freedom on the growth effect of the real exchange rate undervaluation. The marginal growth effects of the real exchange rate undervaluation are enhanced as countries improve the qualities of their economic institutions. The findings are robust with the exclusion of outliers and oil-exporting countries, alternative measures of real exchange rate undervaluation, additional control variables, subcomponents of economic freedom, and multicollinearity between the interaction term and the original variables.